2020
DOI: 10.5688/ajpe7723
|View full text |Cite
|
Sign up to set email alerts
|

A Community Service Organization Focused on the Arts to Develop Empathy in Pharmacy Students

Abstract: Objective. To implement and assess pharmacy students' opinions of a new student organization that uses visual, linguistic, and performing arts to bring emotional support, joy, and healing to patients. Methods. Pro Mé, an on-campus, community-service organization was formed at the Appalachian College of Pharmacy for students with talent or background in the arts. Members organized performances and art events at local assisted living facilities, long-term care facilities, hospitals, mobile medical clinics, schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…were explicitly described; however, close to 90% of the training interventions provided information about the education intervention used to teach students how to better communicate with patients (e.g., role-play, simulations, group discussions, etc. ), which allowed for some training program extrapolation [13,14,[32][33][34][35][36][37][38][39][40][41][42][44][45][46][47][48].…”
Section: Training Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…were explicitly described; however, close to 90% of the training interventions provided information about the education intervention used to teach students how to better communicate with patients (e.g., role-play, simulations, group discussions, etc. ), which allowed for some training program extrapolation [13,14,[32][33][34][35][36][37][38][39][40][41][42][44][45][46][47][48].…”
Section: Training Differencesmentioning
confidence: 99%
“…Emotional empathy, often referred to as clinical empathy, is the ability to share another person's feelings, and focuses on understanding the patient's feelings and using their experiences to skillfully adjust [9,10,23]. Though extrapolated in most of the identified studies, it appears that cognitive training methodologies, those most often employed in academia, were most commonly used to train pharmacy and nursing students in empathy, followed closely by emotional/behavioral frameworks [13,14,[32][33][34][35][36][37][38][39][40][41][42][44][45][46][47][48]. Utilization of emotional/behavioral learning frameworks in empathy training program development may allow for improved understanding and subsequent adjustment of clinical care to better meet the needs of patients.…”
Section: Training Differencesmentioning
confidence: 99%
“…These authors suggested how those with higher levels of empathy have the potential to create better brand positioning. Other studies have looked at empathy in various formats to include the role of the arts in influencing empathy in college students (Preston and Jean-Louis, 2020) along with how empathy mediates avoidance and well-being (Wei et al, 2011).…”
Section: Empathymentioning
confidence: 99%
“…Among pharmacists, only a few studies describe empathy levels using empathy scales (8-11) whereas levels among pharmacy students have been more abundantly measured (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). A few studies among pharmacy students indicate that education in narrative medicine can strengthen the students' competencies in relation to empathy, social understanding, and communication (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%